Decolorization Of Pulp Mill Effluents By White Rot Fungi And Its Correlation To Lignin Degradation - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1998)
Abstract: The dark color of pulp mill effluents mainly due to its high concentration of lignin. The degradation of lignin that cause decolorization of the effluent can be done in part by white rot fungi. Therefore, the purpose of this research is to study the correlation between effluent decolorization with lignin degradation by white rot fungi. Two kinds of effluents were used, i.e. black liquor (BL) and pulp effluent (PE). Decolorization was detected based on the decrease of its optical density (465 nm). Among the species of white rot fungi, Coriolus versicolor was selected based on its higher lignolytic activity, tolerancy to Chlor and high concentration of effluent. This species did decolorize the BL and PE from OD 1.000 to 0.185 and from 0.268 to 0.020, respectively. These values were much higher and faster than those of uninoculated sample or other cultures. It was found that there was a close correlation between effluent decolorization and lignin degradation, because lignin was degraded by C. versicolor during the process of decolorization. The decrease of pH showed that acid compounds were produced during lignin degradation, and some of these acids might be responsible to the decolorization of pulp effluent.